Heterologous and High Production of Ergothioneine in Bacillus licheniformis by Using Genes from Anaerobic Bacteria - Zhe Liu; Fengxu Xiao; Yupeng Zhang; Jiawei Lu; Youran Li; Guiyang Shi (Metabolites)
Purpose: This study aimed to utilize genetically engineered Bacillus licheniformis for the production of ergothioneine (EGT). Given the value of EGT and the application of Bacillus licheniformis in enzyme preparation production, we cloned the key enzymes (EanA and EanB) from Chlorbium limicola. Through gene alignment, new ergothioneine synthase genes (EanAN and EanBN) were identified and then expressed in Bacillus licheniformis to construct strains. Additionally, we investigated the factors influencing the yield of EGT and made a comparison with Escherichia coli. Methods: The relevant genes were cloned and transferred into Bacillus licheniformis. Fermentation experiments were conducted under different conditions for yield analysis, and the stability of this bacterium was also evaluated simultaneously. Results: The constructed strains were capable of producing EGT. Specifically, the yield of the EanANBN strain reached (643.8 ± 135) mg/L, and its stability was suitable for continuous production. Conclusions: Genetically engineered Bacillus licheniformis demonstrates potential in the industrial-scale production of EGT. Compared with Escherichia coli, it has advantages, thus opening up new possibilities for the application and market supply of EGT.